2011
DOI: 10.1007/s11244-011-9637-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mesostructuration of the Beta Zeolite Support on the Properties of Cobalt Catalysts for Fischer–Tropsch Synthesis

Abstract: The effect of mesostructuration of beta zeolite and of metal loading on the properties of cobalt-based catalysts for Fischer-Tropsch synthesis was studied in this work. The most active catalyst was the mesostructured beta zeolite-supported cobalt (10%), which also showed a low selectivity to methane and the lowest olefin/paraffin ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
7
21
0
Order By: Relevance
“…However, an additional band at 563 cm -1 , which are similar to those of the five-membered rings of T-O-T (T = Si or Al) in zeolite crystals 14 Figure 6. The Co 2p profiles of the catalysts display the characteristic doublet corresponding to the spin-orbit coupling (2p 3/2 , 2p 1/2 ) with the most intense Co 2p3/2 peak at binding energies 780.1-780.4 eV 24 , which suggests that the main phase 35 on the catalysts surface is Co 3 O 4 26 , in agreement with the XRD results. To investigate the changes in the surface composition after the addition of ZSM-5 seeds, the atomic ratio of Co/Si is calculated and the obtained quantitative results are displayed in Table 2.…”
Section: Resultssupporting
confidence: 85%
“…However, an additional band at 563 cm -1 , which are similar to those of the five-membered rings of T-O-T (T = Si or Al) in zeolite crystals 14 Figure 6. The Co 2p profiles of the catalysts display the characteristic doublet corresponding to the spin-orbit coupling (2p 3/2 , 2p 1/2 ) with the most intense Co 2p3/2 peak at binding energies 780.1-780.4 eV 24 , which suggests that the main phase 35 on the catalysts surface is Co 3 O 4 26 , in agreement with the XRD results. To investigate the changes in the surface composition after the addition of ZSM-5 seeds, the atomic ratio of Co/Si is calculated and the obtained quantitative results are displayed in Table 2.…”
Section: Resultssupporting
confidence: 85%
“…Several researchers [30][31][32][33][34] have pointed out that cobalt reducibility and species distribution depend on the used support. It has been reported that the reduction of Fe 2 O 3 in H 2 takes place in two (reaction (1) and the combination of (2) and (3)) or three consecutive steps (1, 2 and 3) depending on the temperature used for reduction and on the temperature ramping rate during TPR [35,36].…”
Section: Catalyst Characterization Resultsmentioning
confidence: 99%
“…However, the improvement was insignificant in comparison with the unmodified Beta sample. 7 A comprehensive study on 3 wt% Ru supported on desilicated ZSM-5 and Beta zeolites revealed that the activity for hydrocarbon reactions of FTS products correlates with the extent of support mesoporosity as well as with its acid strength. 8 In spite of the promising results, it is fair to admit that Ru is not the preferred metal of choice for large scale applications due to volatile Ru-carbonyl formation under reaction conditions.…”
mentioning
confidence: 99%